Promoting Gender Equality by Supporting Men's Emotional Flexibility. (March 2021) - Croft, Alyssa; Atkinson, Ciara; May, Alexis M.
Progress toward gender equality has slowed or stalled in recent years, primarily because gender stereotypes and roles are changing more quickly for women than men. Women are increasingly free to behave more like men, whereas a similar freedom for men (to behave more like women) has been slower to emerge. Expectations governing men remain rigid: They are discouraged from showing weakness/vulnerability and encouraged to assert masculinity by demonstrating strength/toughness. These expectations undermine men's emotional flexibility, which not only harms their physical health and well-being but also systematically impedes gender equality efforts. We summarize both the direct and indirect consequences of men's relative emotional inflexibility, as well as cultural and psychological barriers to men's emotional flexibility development. We then provide empirically based policy recommendations for cultivating emotional flexibility in men, which could in turn foster their physical and mental health, undermine traditional gender stereotypes, and promote broader gender equality in the United States.